Reflection as a basis of professional self-development teacher of higher education - Masych, S. (Problems of Engineer-Pedagogical Education, 2018)
Self-development is considered as a continuous process of setting and achieving goals specific person by changing its own activity or conduct oneself based on significant internal aspirations and external influences. A necessary condition for self-development of people, their professional development and growth, is a professional creative self-reflection as a means of opening the human internal forces, driving the intellectual and cultural development of the individual. The profession of teacher requires constant self-development culture within the play, reflection also provides the possibility of opening new meanings as a prerequisite for adequate reproduction values and describes the content and direction-effective formation of his professional competence. Reflection as a universal mechanism of self-transformation and self-development of the human person included in educational activities, is able to provide the task autonomy of each stage of training future teachers. The result of the assimilation of content preparation is reflected in student awareness of their identity, position determining his own academic work, understand the need for self-forming individual style of professional educational activities.